2016
DOI: 10.12688/f1000research.6213.2
|View full text |Cite
|
Sign up to set email alerts
|

Signaling mechanism by the Staphylococcus aureus two-component system LytSR: role of acetyl phosphate in bypassing the cell membrane electrical potential sensor LytS

Abstract: The two-component system LytSR has been linked to the signal transduction of cell membrane electrical potential perturbation and is involved in the adaptation of Staphylococcus aureus to cationic antimicrobial peptides. It consists of a membrane-bound histidine kinase, LytS, which belongs to the family of multiple transmembrane-spanning domains receptors, and a response regulator, LytR, which belongs to the novel family of non-helix-turn-helix DNA-binding domain proteins. LytR regulates the expression of cidAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…We observed that the transcript level of the pta gene and the abundance of the corresponding protein, phosphate acetyltransferase, was lower in S3D14 than in the ancestral ( Figures 6 C and 6E). Although there is no literature that explicitly associates this gene with DAP tolerance or resistance, it has been shown that acetyl phosphate is involved in the phosphorylation of LytR ( Patel and Golemi-Kotra, 2015 ), a member of the two-component system that regulates genes controlling cell apoptosis, autolysin activity, biofilm formation, and is also involved in the adaptation of S . aureus to CAMPs ( Patton et al., 2006 ; Sharma-Kuinkel et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the transcript level of the pta gene and the abundance of the corresponding protein, phosphate acetyltransferase, was lower in S3D14 than in the ancestral ( Figures 6 C and 6E). Although there is no literature that explicitly associates this gene with DAP tolerance or resistance, it has been shown that acetyl phosphate is involved in the phosphorylation of LytR ( Patel and Golemi-Kotra, 2015 ), a member of the two-component system that regulates genes controlling cell apoptosis, autolysin activity, biofilm formation, and is also involved in the adaptation of S . aureus to CAMPs ( Patton et al., 2006 ; Sharma-Kuinkel et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting observation is that many bacterial histidine kinases with several TMDs have been identified in genome-wide bioinformatic analyses [38]. These include the 5-TMD bearing Staphylococcus aureus LytS histidine kinase which acts as a sensor of membrane potential [39]. Another example is Bacillus subtilis DesK, in which TMDs are involved in signaling temperature-induced changes in membrane fluidity [40].…”
Section: Discussionmentioning
confidence: 99%
“…The agr global transcriptional regulator induced a super expression of dltD, a member of the dlt operon (Dunman et al, 2001). Another regulator is the LytSR, a transmembrane electrical potential sensor (Patel and Golemi-Kotra, 2015). AMP cell wall damage is partially due to changes in membrane polarization; therefore, deletion of LytSR increased susceptibility to HNP-1 and tPMPs, Interestingly, no conformational changes were found in mutant cells membrane, indicating an alternative resistance pathway (Yang et al, 2013).…”
Section: Amp Induced Gene Expression/repressionmentioning
confidence: 99%